Customer Engagement as an Intervening Variable of the Influence of Social Media Adoption and Compliance with Islamic Business Ethics on Business Performance - Prawira, Anggun Wida (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to broaden the understanding of the influence of social media adoption on the performance of MSMEs in the city of Surabaya. In 2023, several MSME sectors in the city of Surabaya experienced a decline in sales. MSME sales fell by 25% in October-December 2023 due to lack of promotion and increasing competition for similar products. In the digital era, the use of social media is a way that can be utilized optimally for digital marketing strategies, but many MSMEs do not have sufficient skills and knowledge to implement this strategy. This is an interesting problem to be studied further, regarding how to use social media effectively to drive business performance. The data source used is a primary data source for selected samples. Based on data processing using SmartPLS, the results obtained are that 1) Social Media Adoption is proven to have a significant influence on Business Performance, 2) Islamic Business Ethics Compliance is proven to have a significant influence on Business Performance, 3) Customer Engagement is proven to have a significant influence and relationship with Business Performance, 4) Social Media Adoption has a positive and significant influence on Business Performance through Customer Engagement, 5) Islamic Business Ethics Compliance has a positive and significant influence on Business Performance through Customer Engagement.